(untitled) (International journal of medical sciences, 2025)
Viral hepatitis A (VHA) is an acute viral liver disease caused by the hepatitis A virus (HAV), which belongs to the Picornaviridae family. Genetic variability of the virus plays an important role in the epidemiology of the disease, determining its spread, diagnosis and features of the immune response. The article discusses the genetic structure of the hepatitis A virus, its molecular features and variations, as well as the impact of genetic variability on clinical manifestations and epidemiological aspects. Data on the molecular evolution of the virus, its strains and subtypes are analyzed , which is important for the development of diagnostic, treatment and prevention methods. The introduction of vaccines and new therapeutic approaches based on molecular data will help to improve the effectiveness of the fight against the disease.